Effects of human rhinovirus on epithelial barrier integrity and function in children with asthma - Looi, K.; Buckley, A.; Rigby, P.; Garratt, L.; Iosifidis, T.; Zosky, G.; Larcombe, Alexander; Lannigan, F.; Ling, K.; Martinovich, K.; Kicic-Starcevich, E.; Shaw, N.; et al. (Blackwell Science Ltd, 2018)
Background: Bronchial epithelial tight junctions (TJ) have been extensively assessed in healthy airway epithelium. However, no studies have yet assessed the effect of human rhinovirus (HRV) infection on the expression and resultant barrier function in epithelial tight junctions (TJ) in childhood asthma. Objectives: To investigate the impact of HRV infection on airway epithelial TJ expression and barrier function in airway epithelial cells (AECs) of children with and without asthma. Furthermore, to test the hypothesis that barrier integrity and function is compromised to a greater extent by HRV in AECs from asthmatic children. Methods: Primary AECs were obtained from children with and without asthma, differentiated into air-liquid interface (ALI) cultures and infected with rhinovirus. Expression of claudin-1, occludin and zonula occluden-1 (ZO-1) was assessed via qPCR, immunocytochemistry (ICC), in-cell western (ICW) and confocal microscopy. Barrier function was assessed by transepithelial electrical resistance (TER; RT) and permeability to fluorescent dextran. Results: Basal TJ gene expression of claudin-1 and occludin was significantly upregulated in asthmatic children compared to non-asthmatics; however, no difference was seen with ZO-1. Interestingly, claudin-1, occludin and ZO-1 protein expression was significantly reduced in AEC of asthmatic children compared to non-asthmatic controls suggesting possible post-transcriptional inherent differences. HRV infection resulted in a transient dissociation of TJ and airway barrier integrity in non-asthmatic children. Although similar dissociation of TJ was observed in asthmatic children, a significant and sustained reduction in TJ expression concurrent with both a significant decrease in TER and an increase in permeability in asthmatic children was observed. Conclusion: This study demonstrates novel intrinsic differences in TJ gene and protein expression between AEC of children with and without asthma. Furthermore, it correlates directly the relationship between HRV infection and the resultant dissociation of epithelial TJ that causes a continued altered barrier function in children with asthma.